Insights into the Transition from LIS to Academic Librarianship - McGoveran, Catherine; Thorne, Laura (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
This poster presents the results of a research study examining the transition process between library and information studies (LIS) and academic librarianship in Canada. Using surveys and interviews, the study analyzes data collected from LIS students and recent graduates, new academic librarians, and hiring managers and supervisors. Cette affiche présente les résultats d’une étude examinant le processus de transition entre sciences de l’information & bibliothéconomie (SIB) et l’exercice de la bibliothéconomie universitaire au Canada. À l’aide de sondages et d’entrevues, l’étude analyse les données recueillies auprès des étudiants en SIB et les diplômés récents, les nouveaux bibliothécaires universitaires, et l’embauche de gestionnaires et de superviseurs.